Epidemiology of and Risk Factors for BK Polyomavirus Replication and Nephropathy in Pediatric Renal Transplant Recipients: An International CERTAIN Registry Study. Issue 6 (June 2019) - Höcker, Britta; Schneble, Lukas; Murer, Luisa; Carraro, Andrea; Pape, Lars; Kranz, Birgitta; Oh, Jun; Zirngibl, Matthias; Dello Strologo, Luca; Büscher, Anja; Weber, Lutz T.; Awan, Atif; et al.
Abstract : Background: BK polyomavirus-associated nephropathy (BKPyVAN) constitutes a serious cause of kidney allograft failure, but large-scale data in pediatric renal transplant recipients and a comprehensive analysis of specific risk factors are lacking. Methods: We analyzed the data of 313 patients in the Cooperative European Pediatric Renal Transplant Initiative Registry, with an observation period of 3.3 years (range, 1–5). The net state of immunosuppressive therapy was assessed by the modified Vasudev score. Results: Presumptive BKPyVAN (defined as sustained [>3 wk] high-level BK viremia >10 4 copies/mL) within 5 years posttransplant occurred in 49 (15.8%) of 311 patients, and biopsy-proven BKPyVAN in 14 (4.5%) of 313. BKPyV viremia was observed in 115 (36.7%) of 311 patients, of whom 11 (9.6%) of 115 developed viremia late, that is, after the second year posttransplant. In 6 (12.5%) of 48 patients with high-level viremia and in 3 (21.4%) of 14 with BKPyVAN, this respective event occurred late. According to multivariable analysis, BKPyV viremia and/or BKPyVAN were associated not only with a higher net state of immunosuppression (odds ratio [OR], 1.3; P < 0.01) and with tacrolimus-based versus ciclosporin-based immunosuppression (OR, 3.6; P < 0.01) but also with younger recipient age (OR, 1.1 per y younger; P < 0.001) and obstructive uropathy (OR, 12.4; P < 0.01) as primary renal disease. Conclusions: Uncontrolled BKPyV replication affects a significant proportion of pediatric renal transplant recipients and is associated with unique features of epidemiology and risk factors, such as young recipient age, obstructive uropathy, and overall intensity of immunosuppressive therapy. BKPyV surveillance should be considered beyond 2 years posttransplant in pediatric patients at higher risk. Abstract : Supplemental Digital Content is available in the text.